2003
DOI: 10.1055/s-2003-37725
|View full text |Cite
|
Sign up to set email alerts
|

Zur Diagnostik struktureller Defizite bei Lese-Rechtschreib-Störungen in der klinischen Arbeit: Beziehungen zwischen verschiedenen Leistungsindikatoren

Abstract: The diagnostic procedures used in clinical work are critically evaluated whereby the tests to assess speech intelligibility in noise and dichotic listening, as well as short-term memory appear to be clinically relevant too, however a standardized procedure and age-relevant norms are still needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
2

Year Published

2005
2005
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 3 publications
0
3
0
2
Order By: Relevance
“…However, as no comparison was carried out with children, whose spelling was within the normal range, this study cannot contribute to the clarification of the controversial issue as to whether a a central auditory processing disorder (CAPD) is found more often in children with dyslexia, than in children without this problem (see [see e.g. : 16,20,30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, as no comparison was carried out with children, whose spelling was within the normal range, this study cannot contribute to the clarification of the controversial issue as to whether a a central auditory processing disorder (CAPD) is found more often in children with dyslexia, than in children without this problem (see [see e.g. : 16,20,30].…”
Section: Discussionmentioning
confidence: 99%
“…Thus indications of an auditory perception disorder in existing dyslexia were found. [16,18]. Among others, Suchodoletz et al [28] found contradictory results.…”
Section: Introductionmentioning
confidence: 99%
“…The highest correlation coefficients were shown in the 2nd grade. Accordingly, Möhring et al [16] specified the HLAD as a significant predictor concerning the spelling ability of children of the 2nd grade. Graf [17] and Walter [18] showed that phonological processing and auditory phoneme discrimination ability are a meaningful factor especially in the 2nd grade.…”
Section: Discussionmentioning
confidence: 99%
“…Beeinträchtigte auditive Wahrnehmung und Sprachverarbeitung werden ursächlich im Zusammenhang mit Störungen des Lautund Schriftspracherwerbs diskutiert [1][2][3][4][5][6]. Die Perzeptions-und Produktionsprozesse, die für einen fehlerfreien Sprechakt notwendig sind, basieren auf vielfältigen Kategorisierungsvorgängen.…”
unclassified
“…Durch die neueren Forschungen zu Ursachen der Schriftsprachstö-rungen erzielten basale Funktionsbereiche der Sprech-und Sprachstörungen vermehrt Aufmerksamkeit und rückten unter dem Oberbergriff «auditive Verarbeitungs-und Wahrnehmungsstörungen» und «Störungen der phonologischen Bewusstheit» in den Mittelpunkt des wissenschaftlichen Interesses. Es wurden bei Schulkindern Zusammenhänge zwischen Rechtschreibstörungen und Schwä-chen in der Lautunterscheidung [1,4] sowie Schwächen in der phonologischen Bewusstheit [6,8] …”
unclassified